Material didáctico de traducción a utilizar por profesionales de la salud - Yanet Díaz Pérez; Rosabel Montes de Oca Peña; Yanitza Rodríguez Diéguez; Juana Moreno Pupo; José Manuel Gamayo Serrano; Mayra González Leyva (Correo Científico Médico, 2023)
RESUMEN